Les bovins de la fosse médiévale de Tiya (Éthiopie) : dépôt rituel ou banquet funéraire ? - Joséphine Lesur (Afrique Archéologie Arts, 2005)
The archaeozoological analysis of the faunal remains of the medieval pit of Tiya (Ethiopia) revealed the exclusive presence of bovines. At least four adult animals were found, including males, females and castrated. Results of the analysis testify the kill and the consumption of the animals in situ. These results associated with the anthropological data coming from the stele cemetery adjoining the pit, suggest a possible link between the use of the bovines and the funeral.